Figurative Language Used in Bo Burnham’s Stand-Up Comedy Titled What. - Hansel Christian Handy Junior (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study aims to find out the types of figurative language and the function of the figurative language used in Bo Burnham’s stand-up comedy titled “what.”. The writer conducted this study using the theory of types of figurative language and functions of figurative language by Harris (2018). The writer conducted the study using a qualitative approach method in which he collected and analyzed the data himself. Findings reveal that the figurative language used in "what." comprises simile, metaphor, personification, and allusion, serving to clarify content, provoke interest, and establish associations. This study also found that the types of figurative language used in stand-up comedy depends on the compatibility of the type with the comedic material and the timing and pacing of the performance. It is also found that multiple types of figurative language can appear in a single utterance as it adds layers and creates engagement. It is suggested that future studies consider other forms of humor or alternative theories of figurative language to further diversify and enrich the field.